THE INFLUENCE OF CONTENT MARKETING STRATEGIES AND SERVICE QUALITY ON WORD OF MOUTH THROUGH STUDENT SATISFACTION AT STIM SUKMA MEDAN - Syahrida Khairani; Paham Ginting; Beby Karina Fawzeea Sembiring (RADJA PUBLIKA, 2025)
This study aims to determine and analyze the effect of Content Marketing strategies and service quality on word of mouth through student satisfaction at STIM Sukma Medan. This research is quantitative research. The population in this study were students who enrolled in the 2024/2025 academic year at STIM Sukma Medan. The number of samples in this study were 71 students. The sampling technique used probability sampling, the type of sample design that will be used in this study is random sampling technique. The data analysis technique used is quantitative data analysis. The results showed that the Content Marketing strategy had no significant effect on student satisfaction, but had a positive and significant effect on word of mouth. Student satisfaction and service quality are proven to have a positive and significant effect on word of mouth, and service quality also has a significant effect on student satisfaction. Although service quality does not directly affect word of mouth, through student satisfaction, the effect is significant. In contrast, Content Marketing does not have a significant effect on word of mouth through student satisfaction.